Diagnosis of Type 2 Diabetes: The Experience of Jordanian Patients with Co-existing Depression. (4th March 2015) - Al-Amer, Rasmieh; Ramjan, Lucie; Glew, Paul; Salamonson, Yenna
<x xml:space="preserve">Abstract</x> In Jordan, Type 2 diabetes mellitus (T2DM) is becoming a significant health problem, and a high concomitant rate of depression among this population complicates the situation. This qualitative study explored and described the emotional reactions of Jordanian patients with co-existing depression, on diagnosis of T2DM. Data were collected using semi-structured qualitative interviews from 15 patients with T2DM and depression in 2013. Interviews were audiotaped, translated and then analysed using thematic analysis. A major theme–'Initial reactions to the diagnosis'–emerged with four accompanying sub-themes (Devastation, Mixed Emotions, Denial and Acceptance). Although the majority of participants expressed negative emotional reactions on first diagnosis, a strong religious conviction allowed for acceptance of the diagnosis. Overall, the study findings support that in Arabic countries, spirituality and faith played a key role in promoting acceptance of concomitant comorbidities, and will often be useful in enhancing positive coping strategies among patients with T2DM and depression.